Formulation of kalamansi juice concentrate with packaging material suitability - Fermin, Aileen G.; Quijano, Ana Marie M. (1998)
Green mature kalamansi fruits of medium size, were processed into concentrate by adding sugar and heating to 83°C for 3 minutes. This process was subjected to heat penetration study. Results from using the trapezoidal rule showed that the process was more than adequate. Three formulations were done using different sugar percentages. Physico-chemical and sensory evaluations were done on the products. Results showed that the product containing 132% sugar had the most favorable analysis. This formulation was then standardized. Microbiological, physico-chemical and sensory analyses were done. Results showed that the process obtained had not much variation in terms of the tests that had been conducted. The product was then placed in glass and plastic containers. Packaging material suitability was determined for one month. Microbiological, physico-chemical, and sensory tests were performed weekly for the same period. Results showed that there was not much difference in using both packaging materials based from the tests conducted. The difference was just on the vitamin content in which the plastic had a higher value.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Citrus processing; Kalamansi juice